Evaluation of Development Aspects on the Implementation of Field and Institutional Performance Dashboards at LPKA Class I Palembang - Hadiwijaya, Hendra; Febrianty, Febrianty; Rezania, Rezania (Sinkron : jurnal dan penelitian teknik informatika, 2021)
LPKA Class I Palembang is an institution that enforces the Integrity Zone, WBK, and WBBM. Therefore, one of the technological innovations that will support the implementation is to instill a data-based performance culture through the LPKA Class I Palembang Dashboard. The purpose of this study is to evaluate the development of the dashboard model of government institutions in this case monitoring and reporting on the performance of the fields at LPKA. This evaluation will be included in the development of the dashboard in order to provide optimal net benefits for the management of LPKA Class I Palembang. The research was conducted in 4 stages, namely: determining the research design, identifying dashboard needs, identifying indicators in the development of the Palembang Class I LPKA dashboard model, and formulating a dashboard development model. The dashboard development model was formed based on the results of literature studies and surveys conducted on prospective dashboard users at LPKA Class I Palembang. The survey was conducted on prospective dashboard users, namely structural officials, General Functional Positions, and Certain Functional Positions with a total of 102 employees. The sampling technique is purposive sampling as many as 60 people were directly involved in reporting field performance. The evaluation of the aspects of the LPKA Dashboard shows that from the aspect of presenting Data/Information there are weaknesses in the visual display that is not yet rich in graphics, the unavailability of facilities for predicting future performance conditions, and facilities for causal analysis. The results of this study state that for the aspect of collaboration between users, the benefits that have not been felt are more, namely the exchange of information between users and no conference facilities are available. Meanwhile, in the dashboard performance aspect, there is no link to the administrator.